Spike traits and characteristics of durum and bread wheat genotypes at different growth and developmental stages under water deficit conditions - Moayedi, Ali Akbar; Boyce, Amru Nasrulhaq; Barakbah, Syed Shahar (American-Eurasian Network for Scientific Information, Jordan, 2010)
Drought is an abiotic stress affecting the growth and development in plants and its negative effects during the vegetative and reproductive phases of growth causes different changes in the spike characteristics and traits in durum and bread wheat. A study was carried out to compare and evaluate these differences in spike traits in durum and bread wheat genotypes under different irrigation regimes. The experiments were laid out in split-plot arrangement based on a complete randomized block design with three replications at the Mashhad research stations of the Agricultural and Natural Resource Research Center, Iran. Irrigation regimes were considered as the main plots and included four levels, Subplots were assigned to four durum-promising lines and a bread wheat cultivar. The results indicated that the spikelets spike-1, potential florets spike-1, spike length, spike dry weight, spike partitioning coefficient and spike harvest index significantly decreased under water deficit during floral initiation to anthesis stage. In addition to this, the bread wheat cultivar (Chamran) showed the highest values for spikelets spike -1, spike length, spike dry weight, spike partitioning coefficient and spike harvest index compared to durum wheat genotypes. However, a durum wheat genotype (RASCON37/BEJAH7) also exhibited higher values amongst the durum wheat genotypes. There were significant correlations among spike traits with the strongest association shown between spike partitioning coefficient and spike harvest index. Based on the results, any water limitation during the floral initiation to the anthesis stage have been caused negative effects on spike structure and its related traits. Â© 2010, INSInet Publication.